2000
DOI: 10.1095/biolreprod62.6.1790
|View full text |Cite
|
Sign up to set email alerts
|

Stallion Epididymal Fluid Proteome: Qualitative and Quantitative Characterization; Secretion and Dynamic Changes of Major Proteins1

Abstract: Proteins present in and secreted into the lumen of various regions of the stallion epididymis were characterized qualitatively and quantitatively by two-dimensional electrophoresis. Using this proteomic approach, 201 proteins were found in the lumen and 117 were found that were secreted by the epithelium in various parts of the organ. Eighteen proteins made up 92.6% of the total epididymal secretory activity, lactoferrin (41.2%) and clusterin (24.8%) being the most abundant. Procathepsin D, HE1/CTP (cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(132 citation statements)
references
References 29 publications
1
128
0
3
Order By: Relevance
“…The analysis of seminal plasma proteins using proteomics techniques provides important preliminary data on the abundance of specific proteins in seminal plasma without having to rely on existing antibodies for detection (Fouchécourt et al, 2000;Moura et al, 2007;Martínez-Heredia et al, 2008). This approach has also been successfully used to identify proteins that were associated with fertility in the stallion (Brandon et al, 1999), and the bull (Killian et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of seminal plasma proteins using proteomics techniques provides important preliminary data on the abundance of specific proteins in seminal plasma without having to rely on existing antibodies for detection (Fouchécourt et al, 2000;Moura et al, 2007;Martínez-Heredia et al, 2008). This approach has also been successfully used to identify proteins that were associated with fertility in the stallion (Brandon et al, 1999), and the bull (Killian et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Specific proteins in seminal plasma have been identified as potential markers of male fertility or infertility in the human (Yamakawa et al, 2007;Martínez-Heredia et al, 2008). Comprehensive proteomic analyses have been conducted in the bull (Moura et al, 2007) and stallion (Fouchécourt et al, 2000) to identify proteins in the male accessory gland fluids. In the pig, initial characterization of proteins in boar seminal plasma has begun (Strzezek et al, 2005); however, to date, no seminal plasma proteins identified in boar seminal plasma have been associated with fertility in vivo.…”
mentioning
confidence: 99%
“…The sperm surface is then further modified in the epididymis by sequential exposure to a highly dynamic protein environment created by regionalised secretion and absorption of proteins across the epididymal epithelium. The varying complement of molecules found in the specialised regions of the epididymal tract has been described in numerous species (pig (Dacheux et al 1989, Syntin et al 1996, Guyonnet et al 2009), bull (Belleannee et al 2011, stallion (Fouchecourt et al 2000), rat (Vreeburg et al 1992, Suryawanshi et al 2011 and human (Baker et al 2005, Li et al 2010) including details of all the proteins present (proteome), secreted (secretome) or transcribed (transcriptome), and this information has greatly expanded knowledge of the role of epididymal proteins in sperm maturation (reviewed by Gatti et al (2004) and Dacheux et al (2005Dacheux et al ( , 2009). …”
Section: Physiological Alterations Of the Sperm Surfacementioning
confidence: 99%
“…Associated with decreased embryo quality and lower implantation rates (Morris et al 2002, Henkel et al 2003, sperm nDNA damage is currently thought to result from the attack by reactive oxygen species (ROS) encountered in the testis and during transit through, and storage in, the epididymis (Fouchecourt et al 2000, Vernet et al 2004). The precise mechanism that investigates the oxidative stress that causes the generation of ROS and subsequently leads to sperm DNA damage remains unknown.…”
Section: Introductionmentioning
confidence: 99%